ABSTRACT THE DIFERENCES IN BODY IMAGE BASED ON THE NUTRITIONAL STATUS OF STUDENTS OF SMPN 13 PEKANBARU SAIL DISTRICTS PEKANBARU CITY - Ningsih, Ariyati; ", Nurhasanah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTAdolescents are one of vulnerable groups to negative issues regarding health and nutrition. Nutritional problems suffered by many adolescents are caused by vorius factors, one of which is body image. This research was conducted with the cross-sectional design in which samples were selected with a quota sampling method. Body image was assessed by questionnare BSQ-34. Based on this study of 136 sampless were obtained 68,38% of responden were not satisfied with the sight of their body image and of responden were on normal nutritional status. From the result of the analysis carried out there was significant differences between body image based on the nutritional status (p = 0,020). So, there was a significant differences (p <0,05) among body image basedon the nutritional status of students of SMPN 13 Pekanbaru Sail Districts Pekanbaru City.Keywords : adolescents, body image, the nutritional status